Pengelolaan Wakaf Produktif Tanah Sawah Di Yayasan Islam Pondok Pesantren Miftahul Jannah Jatibaru Kecamatan Jatisari Karawang - Tetep Komarudin; Ahmad Damiri; Jalaludin Jalaludin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The purpose of this researech is to find out how the productive waqf management system of paddy land at the islamic fondation Miftahul Jannah Islamic Boarding School in Jatibaru District Jatisari Karawang, and how the distribution of results from productive waqf management of paddy land at the islamic fondation Miftahul Jannah Islamic Boarding School. Type of research used is field research, us for the approach used in this study is a descriptive-qualitative approach. Nadzir as the manager of waqf in the form of protecting waqf assets, nadzir made the Akta Ikrar Wakaf (AIW) to PPAIW so that have legal power in accordance with statutory regulation. In its management, nadzir uses the anual rental system (long-term rental model and hukr), in principle the payment is direct or cash for year. Waqf manager has never reported the management of waqf to the government or related parties because it does not understand the path or procedures for reporting. Management pattern is still included in the traditional consumptive waqf management pattern. The results of the management of waqf land are approved for boarding operation and for boarding improvements or revairs in school hostels, with a 50% share for the repairs or renovations of boarding schools and 50% for operational costs. Operational cost are divided 75% for the honorarium of the teacher council and 25% for the need of the ATK (Office Stationery).